Use of technetium-99m-pyrophosphate single-photon emission computed tomography/computed tomography in monitoring therapeutic changes of RNA interference therapeutics in patients with hereditary transthyretin amyloid cardiomyopathy - Yi-Hsin Hung; An-Li Yu; Yi-Chieh Chen; Cheng-Hsuan Tsai; Mao-Yuan Su; Chia-Tung Shun; Hsueh-Wen Hsueh; Jimmy Jyh-Ming Juang; Ming-Jen Lee; Ping-Huei Tseng; Chia-Hua Hsu; Sung-Tsang Hsieh; et al. (Journal of the Formosan Medical Association)
Background: RNA interference therapeutics reduce transthyretin production; however, their effect on hereditary transthyretin amyloid cardiomyopathy (ATTR-CA) remains unclear. We aimed to investigate alterations in technetium-99 m (99mTc)-pyrophosphate (PYP) single-photon emission computed tomography/computed tomography (SPECT/CT) outcomes in patients receiving patisiran or vutrisiran. Methods: We retrospectively identified individuals with hereditary ATTR-CA who received patisiran or vutrisiran. First and second 99mTc-PYP SPECT/CT data, including visual grading, planar heart to contralateral lung (H/CL) ratio, and volumetric heart to lung (H/L) ratio were assessed. Results: Eight patients with hereditary ATTR-CA were enrolled. Cohort A included four patients who underwent their first 99mTc-PYP SPECT/CT imaging at the initiation of small interfering RNA (siRNA) treatment, while cohort B comprised four patients who had been receiving siRNA treatment before their first 99mTc-PYP SPECT/CT imaging (median duration 1281 days). Overall, there were numerical reductions in planar H/CL ratio (1.7 ± 0.2 to 1.6 ± 0.1, p = 0.050) and a significant improvement in volumetric H/L ratio (4.0 ± 0.9 to 3.5 ± 0.4, p = 0.035). Although without significance, subgroup analysis showed more pronounced changes in cohort A for both planar H/CL ratio and volumetric H/L ratio (−20.1 ± 12.6% and −17.1 ± 11.4%) compared to cohort B (−3.3 ± 11.2% and −4.3 ± 12.7%). Conclusion: Our results demonstrated a significant decrease in volumetric H/L ratio in hereditary ATTR-CA patients receiving RNA interference therapeutics.